Front Cover: Remarkable Effects of External Magnetic Field on Circularly Polarized Luminescence of EuIII(hfa)3 with Phosphine Chirality (ChemPhysChem 17/2021). Issue 17 (10th August 2021) - Mishima, Kohei; Kaji, Daiki; Fujiki, Michiya; Imai, Yoshitane
Abstract : The Front Cover shows that the luminophore Eu III (hfa)3 (hfa= 1, 1, 1, 5, 5, 5‐hexafluoroacetylacetonate) with chiral phosphine ligands exhibits intense circularly polarized luminescence (CPL) and magnetic circularly polarized luminescence (MCPL). These properties are enhanced due to the synergistic effect afforded by an external magnetic field and a P‐centred chiral organic ligand. More information can be found in the Article by Yoshitane Imai and co‐workers .